The Authority of the Constitutional Court to Adjudicate State Administrative Cases - Marzuki, Abdul Ukas (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2025)
The Constitutional Court (MK) is an institution that has the primary authority to interpret the 1945 Constitution. However, in practice, the Constitutional Court often handles cases related to Administrative Law (TUN), even though its authority normatively falls within the Administrative Court (PTUN) realm. This research aims to analyze the extent of the Constitutional Court's authority in adjudicating Administrative Law cases and the legal implications for the judicial system in Indonesia. This study uses a normative legal method with an approach to legislation, a case approach, and a conceptual approach. Data is obtained from primary legal sources in the form of legislation and Constitutional Court rulings, as well as secondary legal sources such as legal literature and relevant literature. Research results indicate that there is an overlap of authority between the Constitutional Court and the Administrative Court in several cases related to decisions of state organizers, disputes over election results, and legal norm testing that impacts state administration. This creates legal uncertainty and has the potential to undermine the principle of separation of powers within the Indonesian judicial system. Therefore, it is necessary to revise the Law on the Constitutional Court to clarify the boundaries of its authority so that it does not encroach on the realm of administrative law.